SHOPPING ONLINE SEBAGAI GAYA HIDUP - Lestari, Sri Budi (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
The use of internet communication technology can make the world as if in one hand makes electronicbusiness with the concept of Online Shopping at its peak in recent years along with the development ofcommunication technologies over theInternet.How to shop online by using the internet through computers andmobile devices is increasingly popular smartphone can even be said to have become a trend today.Variousconvenience of shopping be the main thing to offer, with enough gadgets available in the home, anyone canalready shop.This study wants to describe the interpretation of the meaning of Online Shopping as lifestyle andobserve several aspects into consideration.Using the media theory of Neil Postman (1992) inStraubhaar et.all(2012: 50) that emphasizes the social system in promoting the culture of technology and dominating also JacquesEllul (1990) which argues that technological developments lead to social dominance and reinforced with thetheory of consumer behavior. Using Interpretive paradigm and descriptive qualitative study,this research found:(1) the perpetrators of online shopping informants know enough about understanding online shop, their educationabove the high school and already has information about online shopping (2) Online shopping for them is not aslifestyle needs in shopping (3) Sources of information based on the experience of friends and environment (4) theage and tastes play a role in making purchasing decisions (5) Encouraged perform online activities from previousoffender (6) the learning process when starting an online shopping activity in addition to the experience of friends,komentardarida wall (7) online shopping is the fulfillment of which provide convenience, practicality, conveniencealready enjoyed today. The study recommends that Internet presence is intended to have all the information neededin people's lives can be accessed quickly, easily and inexpensively. The decision is a personal choice, but thechoice that brings benefits to individuals and society is certainly a wise decision.